Nonsurgical Management of a Large Periapical Lesion: A Case Report - Ghorbanzadeh, Sajedeh; Ashraf, Hengameh; Hosseinpour, Sepanta; Ghorbanzadeh, Fatemeh (Iranian Endodontic Journal, 2017)
This case report describes the non-surgical management of a large cyst-like periapical lesion in the mandible of a 16-year-old female with the chief complaint of periodic swelling and pus drainage from the mandibular anterior region gingivae with no history of pain and traumatic accident in this area. Both mandibular central incisors had extensive caries. Root canals of both mandibular central incisors were filled with calcium hydroxide. After 10 days, endodontic therapy was carried out on both teeth. Clinical and radiographic re-evaluations at 3 and 12 months revealed progressing bone healing. This case report shows that appropriate diagnosis in combination with root canal treatment as a conservative non-surgical approach can lead to complete healing of large lesions without invasive treatments. Keywords: Mandibular Incisor; Nonsurgical Endodontic Therapy; Radicular Cyst